Pharmacy Apps: a new frontier on the digital landscape? - Davies MJ; Collings M; Fletcher W; Mujtaba H (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Background: Over the course of recent years smartphone and tablet technology has evolved rapidly. Similarly, the sphere of healthcare is constantly developing and striving to embrace the newest forms of technology in order to optimise function. Many opportunities for mobile applications (i.e. 'apps') pertinent to the healthcare sector are now emerging. Objective: This study will consider whether registered pharmacists within the United Kingdom (UK) believe it appropriate to use mobile apps during the provision of healthcare within the community setting. Methods: Further to Liverpool John Moores University (LJMU) ethical approval, the 30 item questionnaire was distributed to UK registered pharmacists (n=600) practising within inner city Manchester, Liverpool and Newcastle. The questions were formatted as multiple choice, Likert scales or the open answer type. On questionnaire completion and return, data were analysed using simple frequencies, cross tabulations and non-parametric techniques in the Statistical Package for the Social Sciences (SPSS) (v18). Results: The majority of respondents (78.4% of 211 participants) confirmed that they were confident when using mobile apps on their technology platform. In general, mobile apps were perceived to be useful in facilitating patient consultations (55%) and supporting healthcare education (80%). The main barrier for mobile app use within the workplace was company policy, deemed significant in the case of regional / national chain pharmacies (p<0.001). Pharmacists alluded to the fact that whilst mobile apps demonstrate potential in modern day practise, they will have a greater impact in the future (p<0.001). Conclusion: The data indicate that although pharmacists are supportive of mobile apps in healthcare, a number of factors (i.e. risk, company policy and lack of regulation) may preclude their use in modern day pharmacy practise. Clearly, limitations of the technology must be addressed in order to maximise uptake within healthcare systems. Pharmacists suggest that as the younger generation ages, mobile apps will become a more accepted method by which to manage healthcare in the wider population.